Datos Sobre la Proteína - Nicole C. Agro; Wendy J. Dahl (EDIS, 2016)
Our bodies are made of many proteins. They can make 11 of the amino acids that are needed to make protein but cannot make the other nine, so we must get them from our diet. This 3-page fact sheet is the Spanish-language version of FSHN15-01/FS261: Facts about Protein. It provides an overview of protein basics, roles of proteins in the body, recommended intake, sources of protein, and healthier protein choices. Written by Nicole C. Agro and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, January 2015.